Persepsi Tunanetra terhadap Penggunaan Tongkat di SMK Negeri 7 Padang - Neno Azni Khamil; Asep Ahmad Sopandi (Universitas Negeri Padang, 2018)
The purpose of this study is to describe the perception of the visually impaired on the use of a white cane. The object of this study is visually impaired students in SMK N7 Padang. This study was based on the fact that there were a few visually impaired students who did not use a whire cane to help them walk. This study aims to explorer and describe the perception of the visually impaired on the use of the white cane. The study employed a descriptive qualitative method. The technique of information collection was observation, interview, and documentation. The results show the perception of the visually impaired students on comprehending the use of the white cane is good. The students inclination to use white cane is good, eventhough they are reluctant to use the white cane due to their fear of embarrassment, the readiness of a sighted assistant to guide them.